2022
DOI: 10.3389/fnut.2022.928308
|View full text |Cite
|
Sign up to set email alerts
|

Association between the empirical dietary inflammatory index and cardiorespiratory fitness in Tehranian adults in 2017–2018

Abstract: BackgroundInflammatory-related chronic diseases are increasing in Iran with high consumption of a diet containing pro-inflammatory potential and a sedentary lifestyle. The empirical dietary inflammatory index (EDII) was developed as a tool to assess dietary effects on systemic inflammation. We examined the hypothesis that specific dietary patterns reflecting systemic inflammation are associated with cardiorespiratory fitness (CRF) in Tehranian adults.MethodsThis cross-sectional study was carried out on 270 adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The highest quantity of oxygen that an individual may utilize when participating in intense or strenuous activity is known as VO2 max or maximal oxygen consumption. This measurement is generally considered the best indicator of cardiovascular fitness and aerobic endurance [ 37 ]. Payandeh et al [ 37 ] show that higher adherence to a higher pro-inflammatory potential diet may be associated with less VO 2Max (ml/kg/min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest quantity of oxygen that an individual may utilize when participating in intense or strenuous activity is known as VO2 max or maximal oxygen consumption. This measurement is generally considered the best indicator of cardiovascular fitness and aerobic endurance [ 37 ]. Payandeh et al [ 37 ] show that higher adherence to a higher pro-inflammatory potential diet may be associated with less VO 2Max (ml/kg/min).…”
Section: Discussionmentioning
confidence: 99%
“…This measurement is generally considered the best indicator of cardiovascular fitness and aerobic endurance [ 37 ]. Payandeh et al [ 37 ] show that higher adherence to a higher pro-inflammatory potential diet may be associated with less VO 2Max (ml/kg/min). In contrast, previous results from a case–control study by Scott et al showed the DII score was associated with systemic inflammation increase and less lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Again, an inverse correlation exist between biomarkers of inflammation and cardiorespiratory fitness in certain individuals exposed to exercise [32,33]. The extent to which gender differences and cyclical variations of sex hormones influence immunological responses during exercise is unclear [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…One of the said modes recommends an increase in intensity and duration to improve overall fitness. The following measurement of CRF can provide professionals with valuable information on the motivation for periodically screening all youth patients' regular exercise programs [6]; it can be characterized as a program setting-response relationship. Increases in CRF are associated with a number of health benefits.…”
Section: Introductionmentioning
confidence: 99%